2021
DOI: 10.1108/md-09-2020-1256
|View full text |Cite
|
Sign up to set email alerts
|

Employees' dedication to working from home in times of COVID-19 crisis

Abstract: PurposeAs part of the COVID-19 preventive measures that have entirely impacted individuals' lives worldwide, remote work has been indicated as one of the most challenging aspects that have passed through great adaptation in the past months, highlighting the need for its better understanding. Following the fundamental theoretical frameworks of motivation, the authors argue that remote work tasks and the environment highly determine employees' productivity and satisfaction, which in turn influence their intentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 79 publications
7
43
0
Order By: Relevance
“…To summarize, the objective of our analysis is to relate the main aspects of remote working in SMEs with the productivity perceived by clerks and managers. Our objective is to analyze if aspects like autonomy (Anderson and Kelliher, 2020; Delfino and van der Kolk,2021; Wang et al , 2021), use of technology (Miele and Tirabeni, 2020; Molino et al , 2020), motivation (Prodanova and Kocarev, 2021), trust (Dumitru, 2021; Sposato, 2021), timing in returning the feedback (Delfino and van der Kolk, 2021), physical presence and working following objectives (Wang et al , 2021) have a positive or negative impact on perceived productivity.…”
Section: Organizational and Managerial Aspects Learning Experiences I...mentioning
confidence: 99%
“…To summarize, the objective of our analysis is to relate the main aspects of remote working in SMEs with the productivity perceived by clerks and managers. Our objective is to analyze if aspects like autonomy (Anderson and Kelliher, 2020; Delfino and van der Kolk,2021; Wang et al , 2021), use of technology (Miele and Tirabeni, 2020; Molino et al , 2020), motivation (Prodanova and Kocarev, 2021), trust (Dumitru, 2021; Sposato, 2021), timing in returning the feedback (Delfino and van der Kolk, 2021), physical presence and working following objectives (Wang et al , 2021) have a positive or negative impact on perceived productivity.…”
Section: Organizational and Managerial Aspects Learning Experiences I...mentioning
confidence: 99%
“…Currently, this subject gains even more relevance, since the COVID-19 pandemic brought numerous changes into people's routines, enhancing telework (Mendonça et al, 2022 ) and lighting up discussions about productivity and motivation (Prodanova & Kocarev, 2022 ), together with well-being and mental health of people within this new global reality (Carillo et al, 2021 ; Giorgi et al, 2020 ; Impact et al, 2021 ; Shahriarirad et al, 2021 ). Gamification, during COVID-19 quarantine, showed positive results for the well-being and relief of the tension of people in confinement (Manzano-León et al, 2021 ) and showed a potential positive effect on leveraging both motivation and employee engagement (Pura, 2022 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The remote work format as a motivational factor is studied by Gayane Tovmasyan, Diana Minasyan [5], J. Prodanova and L. Kocarev [6], P. White [7]. Gayane Tovmasyan, Diana Minasyan comes to the following conclusions: most employees are office-oriented; for 12%, remote work is assessed as motivation; during the period of COVID-19, employees re-evaluated the values and significance of motivational factors [5].…”
Section: Literature Reviewmentioning
confidence: 99%